The short run supply response of rubber producersin West Malaysia - Teo, Hui Bek; Tee, Cheam Soon (Agricultural Society, University of Malaya, 1974)
The rubber industry is one of the mainstay of the Malaysian economy covering an acreage of about 4.8 million acres or about 60 percent of the total cultivated acreage (1973). Being such a major industry, a study of the supply response schedule of the Malaysian rubber producers (both the smallholder and the estate sectors) should be of value to those responsible for framing policy measures affecting the rubber industry.